Implementation Standard Precaution of Risky Dental Treatments on Patient with HIV-AIDS in X Community Health Center Yogyakarta - Ikhsan Masyhuri; Tita Ratya Utari; Kusbaryanto Kusbaryanto (Universitas Muhammadiyah Yogyakarta, 2019)
Health services are currently required to do services by following with implementation standard precaution has been established, to create good quality services. Infection that needs to be alert for the dental health care professional is the Human Immunodeficiency Virus. Implementation standard precautions need to be applied to a patient with HIV-AIDS or non-HIV-AIDS infection on risky dental treatments. Qualitative research with case studies. The approach in this study is content analysis. Analyzing the contents of interview results, direct observation, and document observation. Direct observation of PLHIV patients was done perfectly: hand hygiene 46.7%, PPE 95.5%, safe injection 100%, waste and sharp object management 75%, patient care equipment 80%, linen management 100%, environmental management 53.3%, employee health protection 0%, and cough ethics 0%. Results of documents observations related to hand hygiene, patient care equipment, and environmental management are well listed; related to PPE, management of waste and sharp objects, and employee health protection are listed but not yet complete; and related to safe injections, linen management, and cough ethics are not listed on document in X Public Health Center Yogyakarta. Implementation standard precaution overall is quite good and still needs to improved to prevent and control infections, especially HIV-AIDS infections in X Public Health Center Yogyakarta.